Supports d’écriture et gestion de production au quotidien dans le nord de la Gaule (Nerviens, Atrébates) : estampilles et graffiti sur briques et sur tuiles - Christine Hoët-Van Cauwenberghe (Gallia)
The present paper discusses a corpus of marks and graffiti recently recovered on the Nerviorum civitas and Atrebatum civitas. Some of the items presented here have never been published: two bricks from the Bavay Museum as well as an imbrex recovered during a recent excavation in Bavay (Nord) bear ante cocturam marks, respectively graffiti for the former, a stamp for the latter. The bricks found on the forum of Bavay/Bagacum probably formed part of the nearby buildings, while the imbrex comes from a 2nd/3rd c. domus. The paper also discusses an unpublished tile fragment from Dainville (Atrebates), bearing an inscription. In addition, the corpus of stamps from the Titica workshop whose marks were found in Bapaume (Pas-de-Calais) will be completed by an analysis of items recently recovered in Orchies (Nord), Bouvignies (Nord), etc. This new material opens up new avenues as far as onomastics is concerned and will augment the epigraphic corpus from the production sites for architectural elements, in this case found on the consumption site. As to graffiti, these short texts carved in clay, they prove that handwriting was used on a daily basis in the brick and tile workshops in northern Gaul. They also provide information on production or delivery dates and therefore on the management of these workshops.